EFISIENSI KINERJA ALAT GALI MUAT EXCAVATOR CAT 320 PC200 DAN ALAT ANGKUT DUMP TRUCK MITSUBISHI FUSO 220PS PADA KEGIATAN PENGUPASAN LAPISAN OVERBURDEN DI PERTAMBANGAN BATU KAPUR EFISIENSI KINERJA ALAT GALI MUAT EXCAVATOR CAT 320 PC200 DAN ALAT ANGKUT DUMP TRUCK MITSUBISHI FUSO 220PS PADA KEGIATAN PENGUPASAN LAPISAN OVERBURDEN DI PERTAMBANGAN BATU KAPUR - Muhammad El Hakim; Muhammad Husein.Zn; Jarot Wiratama; Ericson, (JTK (Jurnal Teknik Kebumian), 2024)
Â  Abstract : A limestone mining company in South Sumatra has an overburden removal target of 42,400 bcm/month, while the realization of overburden removal is only 21.7% of the target or 9,231.56 bcm/month. The tools used to dismantle the overburden were 1 Cat 320 PC200 excavator and 3 Mitsubishi Fuso 220PS dump trucks. The main work in this activity is digging, loading, moving, unloading, then returning to the initial activity and continuing to repeat. One of the reasons why the production target was not achieved was that the repetitive activities did not run optimally. Based on the cycle time of digging and hauling equipment observed in the field, the productivity of loading and digging tools was 128.98 bcm/hour, while the productivity value of hauling equipment was 15.018 bcm/hour. From the research results, it was found that the match factor of the current pair of units was 0.34, this is very far from ideal. For this reason, it is necessary to add 5 units of Mitsubishi Fuso 220PS dump trucks so that the match factor becomes 0.9. In this way, overburden demolition activities can run more optimally and production can be increased. Keyword: overburden, limestone, productivity, match factor, cycle time